Large-porosity open-graded asphalt mixture as well as preparation method and application thereof
By optimizing the ratio of asphalt mixture and adding materials such as high viscosity and high elasticity modified asphalt, basalt fibers, etc., a stable skeleton structure is formed, which solves the problem of poor performance of traditional drainage asphalt pavement, improves drainage performance and rut resistance, and extends the use life.
Patent Information
- Application Number
- CN202411603041.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional drainage asphalt pavement is prone to water damage problems such as aggregate peeling, pits, and scattering during long-term use. Moreover, its drainage performance, rut resistance and crack resistance are poor, making it difficult to meet the high requirements of the use site. need.
Using high-porosity open-grade asphalt mixture, by optimizing the ratio design of asphalt mixture, high-viscosity and high-elastic modified asphalt, basalt fibers and coarse aggregates with specific particle sizes are added to form a stable framework structure and control porosity. At 22-25%, the strength and toughness of the mixture are improved by high viscosity and high elastic modified asphalt and SBS modifier.
The drainage performance and durability of drainage asphalt pavement, such as rut resistance and crack resistance, avoid strength drop and dust accumulation caused by excessive porosity, and ensure the stability and service life of the pavement performance.
Smart Images

Figure BDA0005128800370000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road engineering, and in particular to a large-void ratio open-graded asphalt mixture and a preparation method and application thereof. Background Art
[0002] Traditional asphalt pavement is an impermeable and dense structure. Rainwater mainly gathers to low-lying areas of the road surface through surface runoff, and then relies on concentrated drainage of the road surface or lateral dispersed flow to be discharged. The concentrated drainage method is to set up water barriers or shoulder ditches on the side of the road to make the road surface water flow gather at a specific section and then be discharged through rapids or water collection wells; while the lateral dispersed flow drainage method is to perform special treatment on the shoulder to allow rainwater to flow freely horizontally.
[0003] Unlike traditional asphalt pavement, drainage asphalt pavement uses a large-void ratio open-graded asphalt mixture to pave the surface, allowing rainwater to penetrate into the asphalt layer and drain naturally along the cross slope of the road surface. Drainage asphalt pavement performs well in drainage, anti-skid and noise reduction, and has become an important means to improve road safety performance. However, under the influence of long-term vehicle loads and environmental factors, especially rain erosion and wheel hydrodynamic pressure, traditional drainage asphalt pavement is prone to water damage such as aggregate peeling, potholes, and scattering, which seriously affects road performance.
[0004] In order to overcome the above defects, the prior art optimizes the gradation of open-graded asphalt mixture with large void ratio (i.e., the pass rate of 4.75mm sieve hole of mixed asphalt is 10-10.2%, and the pass rate of 2.36mm sieve hole is 9.2-9.4%) and improves the performance of modified asphalt, so that even if the porosity of open-graded asphalt mixture with large void ratio is as high as 25-28%, and the laying thickness is only 2-2.5mm, it can improve the defects of traditional drainage asphalt pavement such as weakened drainage and noise reduction functions, easy peeling and looseness to a certain extent. However, too high void ratio often means a reduction in the particle size of coarse aggregate, and the reduction in the particle size of coarse aggregate is likely to lead to a reduction in the strength of asphalt mixture, thereby affecting the road performance and durability of drainage asphalt pavement such as anti-rutting and anti-cracking. In addition, too high porosity is also likely to cause dust and soil to accumulate inside the pavement structure, resulting in a rapid attenuation of the drainage function of the drainage asphalt pavement, which in turn weakens the drainage effect. At the same time, due to the thin paving thickness, the bearing capacity of the drainage asphalt pavement is limited, and it is difficult to withstand the heavy pressure of a large number of vehicles. It is prone to damage such as cracking, peeling and potholes, which also affects the road performance and durability of the drainage asphalt pavement such as anti-rutting and anti-cracking.
[0005] In summary, even by improving the grading of open-graded asphalt mixture with large void ratio and improving the performance of modified asphalt, the drainage asphalt pavement paved therefrom still has poor road performance and durability such as drainage, rutting resistance and cracking resistance, and it is difficult to meet the pavement requirements of places with higher requirements for road performance. Summary of the invention
[0006] One of the purposes of the present invention is to propose a large-void ratio open-graded asphalt mixture, which effectively solves the technical problems of poor drainage performance, rutting resistance, cracking resistance and other road performance and durability of drainage asphalt pavement paved with large-void ratio open-graded asphalt mixture in the prior art by optimizing the mix ratio design and raw materials of the asphalt mixture.
[0007] The second purpose of the present invention is to propose a method for preparing a large-void ratio open-graded asphalt mixture. The preparation method is simple and easy to operate, which is conducive to ensuring the road performance and durability of the drainage asphalt pavement paved with the large-void ratio open-graded asphalt mixture.
[0008] The third purpose of the present invention is to provide an application of a large-void ratio open-graded asphalt mixture, which is used in paving drainage asphalt pavement to ensure the road performance and durability of the prepared drainage asphalt pavement.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] A high-void ratio open-graded asphalt mixture, wherein, by mass percentage, the 13.2 mm sieve pass rate of the high-void ratio open-graded asphalt mixture is 95-100%, the 9.5 mm sieve pass rate is 39.2-39.6%, the 4.75 mm sieve pass rate is 7.0-7.2% and the 2.36 mm sieve pass rate is 6.2-6.4%;
[0011] Calculated by weight, the large void ratio open-graded asphalt mixture includes 6.0-6.2 parts of high-viscosity and high-elasticity modified asphalt, 0.3-0.5 parts of basalt fiber, 95-105 parts of mixed aggregate and 0-2 parts of mineral powder;
[0012] The high-viscosity and high-elasticity modified asphalt has a 60°C composite shear modulus G*>12KPa, a 60°C dynamic viscosity>580,000 Pa·s, and a 25°C elastic recovery>98%;
[0013] Calculated by weight, the mixed aggregate includes 45 to 50 parts of first coarse aggregate of 10 to 15 mm, 45 to 50 parts of second coarse aggregate of 5 to 10 mm, and 5 to 10 parts of fine aggregate of 0 to 3 mm.
[0014] Furthermore, the high-viscosity and high-elastic modified asphalt includes an SBS modifier, and calculated by mass percentage, the added amount of the SBS modifier is ≥10%.
[0015] Furthermore, the first coarse aggregate and the second coarse aggregate are both crushed stone, and the fine aggregate is machine-made sand.
[0016] Furthermore, the crushed stone is any one of diabase, basalt and diorite;
[0017] The crushing value of the crushed stone is ≤18%, the abrasion value is ≤20%, and the apparent relative density is ≥2.6g / cm 3 , water absorption rate ≤1%, firmness ≤8%, adhesion with the high-viscosity and high-elastic modified asphalt ≥ level 5, and in terms of mass percentage, the soft stone content of the crushed stone ≤1%, and the needle-like content ≤8%.
[0018] Furthermore, the machine-made sand is diorite, and the apparent relative density of the machine-made sand is ≥2.5 g / cm 3 , firmness ≤12%, sand equivalent ≥65%.
[0019] Furthermore, the basalt fiber has a diameter of 14-16 μm, a length of 5.5-6.5 mm, a specific gravity of 2.8-3.3, an elongation at break greater than 3.0%, a breaking strength greater than 2000 MPa, and an elastic modulus greater than 80 GPa.
[0020] Furthermore, the mineral powder is limestone, and the apparent density of the mineral powder is ≥2.5g / cm 3 , the hydrophilic coefficient is ≤1%, and the water content of the mineral powder is less than 1% by mass percentage.
[0021] A method for preparing a large-void ratio open-graded asphalt mixture, used for preparing the above-mentioned large-void ratio open-graded asphalt mixture, comprises the following steps:
[0022] A. Preheat the high-viscosity and high-elastic modified asphalt to 180-185°C for use, and preheat the first coarse aggregate, the second coarse aggregate, the fine aggregate and the mineral powder to 200-205°C for use;
[0023] B. stirring the preheated first coarse aggregate, the second coarse aggregate and the fine aggregate to obtain a mixed aggregate;
[0024] C. Mixing the preheated high-viscosity and high-elastic modified asphalt, basalt fiber and mixed aggregate to obtain a mixture;
[0025] D. Stir the preheated mineral powder and the mixed material to obtain a large-void ratio open-graded asphalt mixture.
[0026] Furthermore, the stirring time of step B is 15 to 20 seconds; the stirring temperature of steps B, C and D is 190 to 195° C., and the total stirring time of steps B, C and D is not less than 1 minute.
[0027] Furthermore, the paving thickness of the high-void ratio open-graded asphalt mixture is 4 to 4.5 cm.
[0028] The technical solution provided by the present invention may include the following beneficial effects:
[0029] 1. By adopting the first coarse aggregate of 10-15 mm and the second coarse aggregate of 5-10 mm as coarse aggregate, and designing the proportion of high coarse aggregate and low fine aggregate, the 13.2 mm sieve pass rate of the asphalt mixture is 95-100%, the 9.5 mm sieve pass rate is 39.2-39.6%, the 4.75 mm sieve pass rate is 7.0-7.2%, and the 2.36 mm sieve pass rate is 6.2-6.4%, so that the target void ratio of the asphalt mixture is controlled between 22% and 25%. Under the premise of ensuring the drainage performance of the asphalt mixture, the strength reduction problem caused by excessive porosity and the accumulation of dust and soil inside the pavement structure, which leads to the decline of drainage function and weakened pavement performance, etc., are effectively avoided, thereby improving the drainage performance, anti-rutting and anti-cracking and other road performance and durability of the drainage asphalt pavement.
[0030] 2. As the particle size of the coarse aggregate increases, the pores of the skeleton structure formed by their mutual interlocking also increase, which promotes the improvement of the drainage performance of the asphalt mixture. At the same time, the increase in the particle size of the coarse aggregate also enhances the strength of the skeleton structure, thereby correspondingly improving the overall strength of the asphalt mixture. Therefore, the technical solution uses a first coarse aggregate of 10 to 15 mm and a second coarse aggregate of 5 to 10 mm as coarse aggregate, which not only accurately regulates the gradation of the asphalt mixture and effectively controls the porosity, but also significantly enhances its drainage capacity and strength, thereby optimizing the road performance and durability of the drainage asphalt pavement. In addition, compared with the use of only the second coarse aggregate of 5 to 10 mm, the skeleton strength of the technical solution is higher and the pores are larger, which is more conducive to ensuring the overall performance of the asphalt mixture.
[0031] 3. Abandoning the traditional 3-5mm coarse aggregate, the first coarse aggregate of 10-15mm and the second coarse aggregate of 5-10mm are used to form an open-graded asphalt mixture, ensuring sufficient embedding and locking between the coarse aggregates, and building a stable mechanical support system. At the same time, by excluding coarse aggregates with a particle size of 3-5mm, a more spacious filling space is provided for the asphalt mortar, so that it can fully penetrate and tightly fill the gaps between the coarse aggregates, thereby enhancing the overall density and adhesion of the asphalt mixture. In addition, the above-mentioned ratio design also avoids the possible interference effect between fine aggregates and asphalt mortar, and improves the uniformity and stability of the asphalt mixture. Through the above-mentioned multi-faceted effects, it is helpful to ensure the strength of the asphalt mixture, thereby enhancing the road performance and durability of the drainage asphalt pavement such as anti-rutting and anti-cracking. DETAILED DESCRIPTION
[0032] The technical solution provides a large void ratio open-graded asphalt mixture, wherein, according to mass percentage, the 13.2 mm sieve hole passing rate of the large void ratio open-graded asphalt mixture is 95-100%, the 9.5 mm sieve hole passing rate is 39.2-39.6%, the 4.75 mm sieve hole passing rate is 7.0-7.2% and the 2.36 mm sieve hole passing rate is 6.2-6.4%;
[0033] Calculated by weight, the large void ratio open-graded asphalt mixture includes 6.0-6.2 parts of high-viscosity and high-elasticity modified asphalt, 0.3-0.5 parts of basalt fiber, 95-105 parts of mixed aggregate and 0-2 parts of mineral powder;
[0034] The high-viscosity and high-elasticity modified asphalt has a 60°C composite shear modulus G*>12KPa, a 60°C dynamic viscosity>580,000 Pa·s, and a 25°C elastic recovery>98%;
[0035] Calculated by weight, the mixed aggregate includes 45 to 50 parts of first coarse aggregate of 10 to 15 mm, 45 to 50 parts of second coarse aggregate of 5 to 10 mm, and 5 to 10 parts of fine aggregate of 0 to 3 mm.
[0036] In view of the technical problems that the existing drainage asphalt pavement still has poor drainage performance, rutting resistance, cracking resistance and other road performance and durability, this technical solution proposes a large-void ratio open-graded asphalt mixture. By optimizing the proportion design and raw materials of the asphalt mixture, the asphalt mixture has excellent strength and toughness while meeting the drainage performance, ensuring that the drainage asphalt pavement paved with it has good drainage performance, rutting resistance, cracking resistance and other road performance and durability, meeting actual usage needs.
[0037] Specifically, in the technical solution, by adopting a first coarse aggregate of 10 to 15 mm and a second coarse aggregate of 5 to 10 mm as coarse aggregate, and designing a ratio of high coarse aggregate and low fine aggregate, the 13.2 mm sieve pass rate of the asphalt mixture is 95 to 100%, the 9.5 mm sieve pass rate is 39.2 to 39.6%, the 4.75 mm sieve pass rate is 7.0 to 7.2%, and the 2.36 mm sieve pass rate is 6.2 to 6.4%, so that the target void ratio of the asphalt mixture is controlled between 22 and 25%. Under the premise of ensuring the drainage performance of the asphalt mixture, the strength reduction problem caused by excessive porosity and the accumulation of dust and soil inside the pavement structure, which in turn leads to the decline of drainage function and weakened pavement performance, etc., are effectively avoided, thereby improving the drainage performance, anti-rutting and anti-cracking and other road performance and durability of the drainage asphalt pavement.
[0038] Furthermore, as the particle size of the coarse aggregate increases, the pores of the skeleton structure formed by their mutual interlocking also increase, which promotes the improvement of the drainage performance of the asphalt mixture. At the same time, the increase in the particle size of the coarse aggregate also enhances the strength of the skeleton structure, thereby correspondingly improving the overall strength of the asphalt mixture. Therefore, the technical solution uses a first coarse aggregate of 10 to 15 mm and a second coarse aggregate of 5 to 10 mm as coarse aggregate, which not only accurately regulates the gradation of the asphalt mixture and effectively controls the porosity, but also significantly enhances its drainage capacity and strength, thereby optimizing the road performance and durability of the drainage asphalt pavement. In addition, compared with the use of only a second coarse aggregate of 5 to 10 mm, the skeleton strength of the technical solution is higher and the pores are larger, which is more conducive to ensuring the overall performance of the asphalt mixture.
[0039] Furthermore, the technical solution abandons the traditional 3-5 mm coarse aggregate and adopts 10-15 mm first coarse aggregate and 5-10 mm second coarse aggregate to form an open-graded asphalt mixture, ensuring sufficient embedding and locking between the coarse aggregates and building a stable mechanical support system. At the same time, by excluding coarse aggregates with a particle size of 3-5 mm, a more spacious filling space is provided for the asphalt mortar, so that it can fully penetrate and tightly fill the gaps between the coarse aggregates, thereby enhancing the overall density and adhesion of the asphalt mixture. In addition, the above-mentioned ratio design also avoids the possible interference effect between fine aggregate and asphalt mortar, and improves the uniformity and stability of the asphalt mixture. Through the above-mentioned multi-faceted effects, it is helpful to ensure the strength of the asphalt mixture, thereby enhancing the road performance and durability of the drainage asphalt pavement such as anti-rutting and anti-cracking.
[0040] It should be noted that since the maximum particle size of the asphalt mixture in this technical solution is 13.2 mm, according to the relevant requirements of the "Highway Asphalt Pavement Design Specification JTGD50-2017", the laying thickness of the asphalt mixture should not be less than 2.5 to 3 times the nominal maximum particle size, that is, the laying thickness of the asphalt mixture in this technical solution should not be less than 3.3 to 4 cm, further ensuring the performance of the drainage asphalt pavement paved with the asphalt mixture.
[0041] More specifically, the raw materials of the asphalt mixture of the present technical solution also include basalt fiber. Among them, basalt fiber drives the high-viscosity and high-elasticity modified asphalt to tightly wrap the aggregate surface by absorbing asphalt, increasing the thickness of the asphalt oil film, thereby significantly increasing the strength and durability of the asphalt mixture. In addition, the uniform distribution of basalt fiber in the asphalt mixture and the three-phase composite structure constructed with high-viscosity and high-elasticity modified asphalt and mineral materials (i.e., the first coarse aggregate, the second coarse aggregate, the fine aggregate and the mineral powder) can increase its own reinforcement effect, thereby greatly improving the road performance of the asphalt mixture such as anti-rutting and anti-cracking, and significantly reducing the risk of early disease of drainage asphalt pavement, and extending the service life of drainage asphalt pavement.
[0042] In addition, given the high porosity of the mixture, higher requirements are placed on the adhesion between asphalt and aggregate. Therefore, this technical solution also adds mineral powder to the asphalt mixture, which can not only fill the gaps in the skeleton formed by the mutual extrusion of aggregates to form a more stable skeleton, but also absorb free asphalt to form asphalt mortar, significantly improving the thickness of the asphalt film and the adhesion between aggregates, enhancing the anti-aging ability, and improving the overall stability of the asphalt mixture.
[0043] Furthermore, due to the small specific surface area of coarse aggregate, the contact area with high-viscosity and high-elasticity modified asphalt is limited. When ordinary modified asphalt is used, the adhesion to coarse aggregate is insufficient. In addition, the drainage asphalt pavement formed by the asphalt mixture as the surface layer is easily continuously affected by the complex road environment and natural environment, and its target void ratio reaches 22-25%, which increases the contact area with the external environment, making the asphalt mixture under the action of dynamic water pressure and ultraviolet rays, the aging phenomenon is aggravated. Therefore, the technical solution particularly uses high-viscosity and high-elasticity modified asphalt to ensure the performance of the asphalt mixture. The 60℃ dynamic viscosity is an important parameter reflecting the ability of road asphalt to resist permanent deformation at high temperature, the 25℃ elastic recovery is an important parameter reflecting the toughness of road asphalt, and the 60℃ composite shear modulus is an important parameter reflecting the strength of road asphalt. This technical solution selects high-viscosity and high-elastic modified asphalt with a 60℃ composite shear modulus G*>12KPa, a 60℃ dynamic viscosity>580,000 Pa·s, and a 25℃ elastic recovery>98% as raw material, which is beneficial to improving the adhesion of high-viscosity and high-elastic modified asphalt to coarse aggregate, giving the mixed asphalt high strength and high toughness, and ensuring the anti-rutting and anti-cracking properties of the drainage asphalt pavement.
[0044] It is further explained that the high-viscosity and high-elasticity modified asphalt includes an SBS modifier, and calculated by mass percentage, the added amount of the SBS modifier is ≥10%.
[0045] When the amount of SBS modifier added is ≥10%, it can effectively improve the strength and toughness of asphalt mixture, and give the asphalt mixture better road performance such as anti-rutting, anti-cracking, anti-fatigue and anti-water damage. In addition, when the amount of SBS modifier added is ≥10%, it is helpful to provide sufficient viscosity for high-viscosity and high-elasticity modified asphalt, making it more encapsulating and bonding to aggregates, further improving the performance of asphalt mixture.
[0046] It is further explained that the first coarse aggregate and the second coarse aggregate are both crushed stone, and the fine aggregate is machine-made sand.
[0047] Since crushed stone has higher strength and greater polishing value, in order to further ensure the relevant performance of the drainage asphalt pavement, the first coarse aggregate and the second coarse aggregate of the technical solution are both crushed stone.
[0048] Since machine-made sand is clean, free of impurities, has good angularity and high roughness, and fine aggregates with good angularity have strong adhesion to asphalt, which can improve the shear resistance of the mixture, therefore, this technical solution preferably uses machine-made sand as fine aggregate in asphalt mixture.
[0049] It is further specified that the crushed stone is any one of diabase, basalt and diorite;
[0050] The crushing value of the crushed stone is ≤18%, the abrasion value is ≤20%, and the apparent relative density is ≥2.6g / cm 3 , water absorption rate ≤1%, firmness ≤8%, adhesion with the high-viscosity and high-elasticity modified asphalt ≥ level 5, and in terms of mass percentage, the soft stone content of the crushed stone ≤1%, and the needle-like content ≤8%.
[0051] Coarse aggregate is the main body of the asphalt mixture skeleton structure. It is required to have sufficient firmness, wear resistance, crushing value and abrasion value, square particle shape, sharp edges and corners, indicating roughness, dryness and cleanliness, good adhesion and hydrophobicity, so as to form a good embedded structure and a stable main skeleton, and improve the overall structural stability of the asphalt mixture. This technical solution optimizes the type and performance parameters of crushed stone, which is more conducive to the use of crushed stone as coarse aggregate in asphalt mixture to enhance the skeleton structure.
[0052] It should be noted that soft stone refers to stone that is soft in texture and easy to process.
[0053] Further explanation: the machine-made sand is diorite, and the apparent relative density of the machine-made sand is ≥2.5g / cm3 , firmness ≤12%, sand equivalent ≥65%.
[0054] Fine aggregate is an important factor affecting the shear resistance of asphalt mixture. Fine aggregate forms asphalt mortar with asphalt, which plays a role in filling and transferring load in asphalt mixture. This technical solution optimizes the type and performance parameters of machine-made sand, which is more conducive to the use of machine-made sand as fine aggregate in asphalt mixture to play a role in filling and transferring load.
[0055] It is further explained that the basalt fiber has a diameter of 14-16 μm, a length of 5.5-6.5 mm, a specific gravity of 2.8-3.3, an elongation at break greater than 3.0%, a breaking strength greater than 2000 MPa, and an elastic modulus greater than 80 GPa.
[0056] Limiting the diameter of basalt fiber to the range of 14 to 16 μm makes the basalt fiber have a smaller size, which is not only conducive to its uniform distribution in the asphalt mixture, thereby improving the overall performance of the asphalt mixture, but also can increase the contact area between basalt fiber and high-viscosity and high-elastic modified asphalt, improve the interface bonding force, and improve the strength and toughness of the asphalt mixture.
[0057] In addition, the length of basalt fiber is limited to the range of 5.5 to 6.5 mm, so that basalt fiber can form an effective three-dimensional network structure in the asphalt mixture, which can not only improve the strength and toughness of the asphalt mixture, but also improve its impact resistance and wear resistance.
[0058] Furthermore, the technical solution optimizes the density, elongation at break, breaking strength and elastic modulus of basalt fiber, which can effectively ensure that it plays a "reinforcement" role in asphalt mixture and provides more stable restraint force to the asphalt mixture.
[0059] Further description: the mineral powder is limestone, and the apparent density of the mineral powder is ≥2.5g / cm 3 , the hydrophilic coefficient is ≤1%, and the water content of the mineral powder is less than 1% by mass percentage.
[0060] Selecting mineral powder obtained by grinding limestone and optimizing its apparent density, hydrophilicity coefficient and water content can help significantly increase the thickness of the asphalt oil film and enhance the adhesion between aggregates, thereby more effectively enhancing the strength and stability of the asphalt mixture.
[0061] A method for preparing a large-void ratio open-graded asphalt mixture, used for preparing the above-mentioned large-void ratio open-graded asphalt mixture, comprises the following steps:
[0062] A. Preheat the high-viscosity and high-elastic modified asphalt to 180-185°C for use, and preheat the first coarse aggregate, the second coarse aggregate, the fine aggregate and the mineral powder to 200-205°C for use;
[0063] B. stirring the preheated first coarse aggregate, the second coarse aggregate and the fine aggregate to obtain a mixed aggregate;
[0064] C. Mixing the preheated high-viscosity and high-elastic modified asphalt, basalt fiber and mixed aggregate to obtain a mixture;
[0065] D. Stir the preheated mineral powder and the mixed material to obtain a large-void ratio open-graded asphalt mixture.
[0066] The technical solution also proposes a method for preparing a large-void ratio open-graded asphalt mixture, which has simple steps and strong operability, and is conducive to avoiding weakening the relevant properties of the asphalt mixture during the preparation process.
[0067] Specifically, in this technical solution, the high-viscosity and high-elasticity modified asphalt is preheated to 180-185°C for standby use, which can ensure that the asphalt is in a fluid state during the mixing process, which is conducive to full mixing with the aggregate and improving the uniformity of the mixture. Preheating the high-viscosity and high-elasticity modified asphalt can also reduce the aging of the high-viscosity and high-elasticity modified asphalt caused by too low temperature during the mixing process, thereby extending the service life of the asphalt mixture.
[0068] It is further specified that the stirring time of step B is 15 to 20 seconds; the stirring temperature of steps B, C and D is 190 to 195° C., and the total stirring time of steps B, C and D is not less than 1 minute.
[0069] The stirring time of step B is limited to 15 to 20 seconds, so that the coarse aggregate and the fine aggregate are fully mixed in the preheated state to form a uniform mixed aggregate, which is conducive to the uniform distribution of asphalt and fiber in the subsequent steps. In addition, by controlling the total stirring time, it is conducive to eliminating bubbles and voids in the mixture, improving its density and uniformity, and thus ensuring the relevant performance of the asphalt mixture.
[0070] It is further explained that the paving thickness of the large void ratio open-graded asphalt mixture is 4 to 4.5 cm.
[0071] This technical solution helps to ensure the performance of the drainage asphalt pavement paved therewith by optimizing the paving thickness of the open-graded asphalt mixture with a large void ratio.
[0072] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0073] Example 1
[0074] In this embodiment, the gradation of the open-graded asphalt mixture with large void ratio is calculated by mass percentage as follows: the passing rate of 13.2 mm sieve hole is 95.7%, the passing rate of 9.5 mm sieve hole is 39.4%, the passing rate of 4.75 mm sieve hole is 7.0% and the passing rate of 2.36 mm sieve hole is 6.2%; calculated by mass parts, the open-graded asphalt mixture with large void ratio includes 6.2 parts of high-viscosity and high-elasticity modified asphalt, 0.4 parts of basalt fiber, 98 parts of mixed aggregate and 2 parts of limestone mineral powder; calculated by mass parts, the mixed aggregate includes 10 to 1 45 parts of 5mm crushed stone, 45 parts of 5-10mm crushed stone and 8 parts of 0-3mm machine-made sand; the high-viscosity and high-elasticity modified asphalt includes SBS modifier, and the addition amount of SBS modifier is 10% calculated by mass percentage; the 60℃ composite shear modulus G* of the high-viscosity and high-elasticity modified asphalt is 12.88kPa, the 60℃ dynamic viscosity is 600,000 Pa·s, and the 25℃ elastic recovery is 99.4%; the crushed stone is diabase, the crushing value of the crushed stone is 8.0%, the abrasion value is 9.2%, and the apparent relative density is 2.954g / cm 3 The water absorption rate is 0.72%, the firmness is 2.0%, the adhesion with high-viscosity and high-elastic modified asphalt is level 5, and according to the mass percentage, the soft stone content of the crushed stone is 1%, and the needle-like content is 3.1%; the machine-made sand is diorite, and the apparent relative density of the machine-made sand is 2.940g / cm 3 , firmness is 2.5%, sand equivalent is 67%; the diameter of basalt fiber is 14μm, length is 5.5mm, specific gravity is 2.8, elongation at break is 3.1%, breaking strength is 2700Mpa, elastic modulus is 95Gpa; the apparent relative density of mineral powder is 2.719g / cm 3 , the hydrophilic coefficient is 0.6, and the water content of the mineral powder is 0.5% by mass.
[0075] The preparation method of a large void ratio open-graded asphalt mixture in this embodiment comprises the following steps:
[0076] A. Preheat the high-viscosity and high-elastic modified asphalt to 180℃ for standby use, and preheat the 10-15mm crushed stone, 5-10mm crushed stone, 0-3mm machine-made sand and mineral powder to 205℃ for standby use;
[0077] B. Mix the preheated 10-15 mm crushed stone, 5-10 mm crushed stone and 0-3 mm machine-made sand for 15 seconds to obtain mixed aggregate;
[0078] C. stirring the preheated high-viscosity and high-elastic modified asphalt, basalt fiber and mixed aggregate for 45 seconds to obtain a mixture;
[0079] D. Stir the preheated mineral powder and mixed material for 40 seconds to obtain a large void ratio open-graded asphalt mixture.
[0080] Example 2
[0081] In this embodiment, the gradation of the open-graded asphalt mixture with large void ratio is calculated by mass percentage as follows: the passing rate of 13.2 mm sieve hole is 95.8%, the passing rate of 9.5 mm sieve hole is 39.3%, the passing rate of 4.75 mm sieve hole is 7.1% and the passing rate of 2.36 mm sieve hole is 6.1%; calculated by mass parts, the open-graded asphalt mixture with large void ratio includes 6.1 parts of high-viscosity and high-elasticity modified asphalt, 0.4 parts of basalt fiber, 98 parts of mixed aggregate and 2 parts of limestone mineral powder; calculated by mass parts, the mixed aggregate includes 10 to 1 46 parts of 5mm crushed stone, 46 parts of 5-10mm crushed stone and 6 parts of 0-3mm machine-made sand; the high-viscosity and high-elasticity modified asphalt includes SBS modifier, and the addition amount of SBS modifier is 12% calculated by mass percentage; the 60℃ composite shear modulus G* of the high-viscosity and high-elasticity modified asphalt is 12.78kPa, the 60℃ dynamic viscosity is 600,000 Pa·s, and the 25℃ elastic recovery is 99.5%; the crushed stone is basalt, the crushing value of the crushed stone is 8.1%, the abrasion value is 9.1%, and the apparent relative density is 2.955g / cm 3 The water absorption rate is 0.72%, the firmness is 2.0%, the adhesion with high-viscosity and high-elastic modified asphalt is level 5, and according to the mass percentage, the soft stone content of the crushed stone is 1%, and the needle-like content is 3.3%; the machine-made sand is diorite, and the apparent relative density of the machine-made sand is 2.939g / cm 3 , firmness is 2.5%, sand equivalent is 67%; the diameter of basalt fiber is 14μm, length is 5.5mm, specific gravity is 2.9, elongation at break is 3.1%, breaking strength is 2900Mpa, elastic modulus is 100Gpa; the apparent relative density of mineral powder is 2.719g / cm 3 , the hydrophilic coefficient is 0.6, and the water content of the mineral powder is 0.5% by mass.
[0082] The preparation method of a large void ratio open-graded asphalt mixture in this embodiment comprises the following steps:
[0083] A. Preheat the high-viscosity and high-elastic modified asphalt to 185℃ for standby use, and preheat 10-15mm crushed stone, 5-10mm crushed stone, 0-3mm machine-made sand and mineral powder to 200℃ for standby use;
[0084] B. Mix the preheated 10-15 mm crushed stone, 5-10 mm crushed stone and 0-3 mm machine-made sand for 20 seconds to obtain mixed aggregate;
[0085] C. Stirring the preheated high-viscosity and high-elastic modified asphalt, basalt fiber and mixed aggregate for 20 seconds to obtain a mixture;
[0086] D. Stir the preheated mineral powder and the mixture for 48 seconds to obtain a large-void open-graded asphalt mixture.
[0087] Example 3
[0088] In this embodiment, according to the mass percentage, the gradation of the open-graded asphalt mixture with large void ratio is 95.9% for the 13.2 mm sieve hole pass rate, 39.3% for the 9.5 mm sieve hole pass rate, 7.1% for the 4.75 mm sieve hole pass rate and 6.1% for the 2.36 mm sieve hole pass rate; according to the mass percentage, the open-graded asphalt mixture with large void ratio includes 6.0 parts of high-viscosity and high-elasticity modified asphalt, 0.5 parts of basalt fiber, 100 parts of mixed aggregate and 1 part of limestone powder; according to the mass percentage, the mixed aggregate includes 45 parts of 10-15 mm crushed stone, 50 parts of 5-10 mm crushed stone and 5 parts of 0-3 mm machine-made sand; the high-viscosity and high-elasticity modified asphalt includes SBS modified The SBS modifier is added in an amount of 11% by mass percentage; the 60℃ composite shear modulus G* of the high-viscosity and high-elastic modified asphalt is 12.78kPa, the 60℃ dynamic viscosity is 600,000 Pa·s, and the 25℃ elastic recovery is 99.5%; the crushed stone is diorite, the crushing value of the crushed stone is 8.5%, the abrasion value is 9.4%, the apparent relative density is 2.957g / cm3, the water absorption rate is 0.70%, the firmness is 2.0%, and the adhesion with the high-viscosity and high-elastic modified asphalt is level 5, and according to the mass percentage, the soft stone content of the crushed stone is 1%, and the needle-like content is 2.9%; the machine-made sand is diorite, and the apparent relative density of the machine-made sand is 2.938g / cm 3 , firmness is 2.4%, sand equivalent is 68%; the diameter of basalt fiber is 15μm, length is 6.5mm, specific gravity is 3.0, elongation at break is 3.1%, breaking strength is 2800Mpa, elastic modulus is 100Gpa; the apparent relative density of mineral powder is 2.713g / cm 3 , the hydrophilic coefficient is 0.6, and the water content of the mineral powder is 0.5% by mass.
[0089] The preparation method of a large void ratio open-graded asphalt mixture in this embodiment comprises the following steps:
[0090] A. Preheat the high-viscosity and high-elastic modified asphalt to 185℃ for standby use, and preheat 10-15mm crushed stone, 5-10mm crushed stone, 0-3mm machine-made sand and mineral powder to 200℃ for standby use;
[0091] B. Mix the preheated 10-15 mm crushed stone, 5-10 mm crushed stone and 0-3 mm machine-made sand for 20 seconds to obtain mixed aggregate;
[0092] C. Stirring the preheated high-viscosity and high-elastic modified asphalt, basalt fiber and mixed aggregate for 50 seconds to obtain a mixture;
[0093] D. Stir the preheated mineral powder and mixed material for 40 seconds to obtain a large void ratio open-graded asphalt mixture.
[0094] The asphalt mixtures prepared in Examples 1 to 3 were used for pavement paving, and the implementation thickness is shown in Table 1. The paved drainage asphalt pavement was tested for relevant performance in accordance with the standards specified in the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) and the "Field Test Procedure for Highway Roadbed and Pavement" (JTG 3450-2019). It was compared with the existing drainage asphalt pavement paved with traditional asphalt mixtures and the drainage asphalt pavement paved with super-large void asphalt mixtures prepared using patent CN115043614A. The results are shown in Table 1 below.
[0095] Table 1 Related performance test results of drainage asphalt pavement
[0096]
[0097] The performance test indicators of the drainage asphalt pavement paved with a large-void open-graded asphalt mixture according to the technical solution are superior to those of the traditional drainage asphalt pavement, effectively solving the water damage problems of aggregate peeling, potholes, and scattering that are prone to occur in traditional large-void asphalt mixtures; at the same time, compared with the asphalt pavement paved with super-large-void asphalt mixtures, it has great advantages in water permeability coefficient and rutting dynamic stability indicators, solving the technical problems of rapid attenuation of drainage performance and insufficient rutting resistance of asphalt pavements paved with super-large-void asphalt mixtures, so that the asphalt mixture has better drainage performance, rutting resistance, cracking resistance and other road performance and durability when forming a drainage asphalt pavement.
[0098] It should be noted that, calculated by mass percentage, the gradation of the traditional asphalt mixture is 98.0% for 13.2mm sieve hole, 70.5% for 9.5mm sieve hole, 22.3% for 4.75mm sieve hole and 14.2% for 2.36mm sieve hole; calculated by mass parts, the traditional asphalt mixture includes 4.8 parts of SBS modified asphalt, 0.15 parts of lignin fiber, 98 parts of mixed aggregate and 2 parts of limestone mineral powder; calculated by mass parts According to calculation, the mixed aggregate includes 41 parts of crushed stone with a diameter of 10-15 mm, 45 parts of crushed stone with a diameter of 5-10 mm, and 10 parts of machine-made sand with a diameter of 0-3 mm; the SBS modified asphalt includes an SBS modifier, and the amount of the SBS modifier added is 5% according to the mass percentage; the needle penetration of the SBS modified asphalt is 53, the ductility is 33, and the softening point is 82; the crushed stone is diorite, the crushing value of the crushed stone is 8.5%, the abrasion value is 9.4%, and the apparent relative density is 2.961 g / cm 3The water absorption rate is 0.72%, the firmness is 2.0%, the adhesion with SBS modified asphalt is level 5, and according to the mass percentage, the soft stone content of the crushed stone is 0.8%, and the needle-like content is 2.8%; the machine-made sand is diorite, and the apparent relative density of the machine-made sand is 2.941g / cm 3 , firmness is 2.4%, sand equivalent is 65%; apparent relative density of mineral powder is 2.712g / cm 3 , the hydrophilic coefficient is 0.6, and the water content of the mineral powder is 0.5% by mass.
[0099] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A high-void ratio open-graded asphalt mixture, characterized in that: According to mass percentage, the 13.2mm sieve hole passing rate of the large void ratio open-graded asphalt mixture is 95-100%, the 9.5mm sieve hole passing rate is 39.2-39.6%, the 4.75mm sieve hole passing rate is 7.0-7.2% and the 2.36mm sieve hole passing rate is 6.2-6.4%; Calculated by weight, the large void ratio open-graded asphalt mixture includes 6.0-6.2 parts of high-viscosity and high-elasticity modified asphalt, 0.3-0.5 parts of basalt fiber, 95-105 parts of mixed aggregate and 0-2 parts of mineral powder; The high-viscosity and high-elasticity modified asphalt has a 60°C composite shear modulus G*>12KPa, a 60°C dynamic viscosity>580,000 Pa·s, and a 25°C elastic recovery>98%; Calculated by weight, the mixed aggregate includes 45 to 50 parts of first coarse aggregate of 10 to 15 mm, 45 to 50 parts of second coarse aggregate of 5 to 10 mm, and 5 to 10 parts of fine aggregate of 0 to 3 mm.
2. The high-void ratio open-graded asphalt mixture according to claim 1, characterized in that: The high-viscosity and high-elastic modified asphalt includes an SBS modifier, and calculated by mass percentage, the added amount of the SBS modifier is ≥10%.
3. The high-void ratio open-graded asphalt mixture according to claim 1, characterized in that: The first coarse aggregate and the second coarse aggregate are both crushed stone, and the fine aggregate is machine-made sand.
4. The high-void ratio open-graded asphalt mixture according to claim 3, characterized in that: The crushed stone is any one of diabase, basalt and diorite; The crushing value of the crushed stone is ≤18%, the abrasion value is ≤20%, and the apparent relative density is ≥2.6g / cm 3 , water absorption rate ≤1%, firmness ≤8%, adhesion with the high-viscosity and high-elasticity modified asphalt ≥ level 5, and in terms of mass percentage, the soft stone content of the crushed stone ≤1%, and the needle-like content ≤8%.
5. The open-graded asphalt mixture with large void ratio according to claim 3, characterized in that: The machine-made sand is diorite, and the apparent relative density of the machine-made sand is ≥2.5g / cm 3 , firmness ≤12%, sand equivalent ≥65%.
6. The high-void ratio open-graded asphalt mixture according to claim 1, characterized in that: The basalt fiber has a diameter of 14-16 μm, a length of 5.5-6.5 mm, a specific gravity of 2.8-3.3, a breaking elongation greater than 3.0%, a breaking strength greater than 2000 MPa, and an elastic modulus greater than 80 GPa.
7. The high-void ratio open-graded asphalt mixture according to claim 1, characterized in that: The mineral powder is limestone, and the apparent density of the mineral powder is ≥2.5g / cm 3 , the hydrophilic coefficient is ≤1%, and the water content of the mineral powder is less than 1% by mass percentage.
8. A method for preparing a high-void ratio open-graded asphalt mixture, characterized in that: The method for preparing the open-graded asphalt mixture with large void ratio according to any one of claims 1 to 7 comprises the following steps: A. Preheat the high-viscosity and high-elastic modified asphalt to 180-185°C for use, and preheat the first coarse aggregate, the second coarse aggregate, the fine aggregate and the mineral powder to 200-205°C for use; B. stirring the preheated first coarse aggregate, the second coarse aggregate and the fine aggregate to obtain a mixed aggregate; C. Mixing the preheated high-viscosity and high-elastic modified asphalt, basalt fiber and mixed aggregate to obtain a mixture; D. Stir the preheated mineral powder and the mixed material to obtain a large-void ratio open-graded asphalt mixture.
9. The high-void ratio open-graded asphalt mixture according to claim 8, characterized in that: The stirring time of step B is 15 to 20 seconds; the stirring temperature of steps B, C and D is 190 to 195° C., and the total stirring time of steps B, C and D is not less than 1 minute.
10. Application of a high-void ratio open-graded asphalt mixture in drainage asphalt pavement, characterized in that: The paving thickness of the large-void ratio open-graded asphalt mixture is 4 to 4.5 cm.
Citation Information
Cited By
Mute asphalt mixture as well as preparation method and application thereof
CN121021047A
